2013
DOI: 10.4081/ejh.2013.e30
|View full text |Cite
|
Sign up to set email alerts
|

KiSS1 inhibits growth and invasion of osteosarcoma cells through inhibition of the MAPK pathway

Abstract: As a metastasis suppressor, KiSS1 has been implicated in numerous human cancers. However, recent studies have demonstrated that KiSS1 promotes tumor growth and metastasis in breast cancer, and it is unclear about the expression and function of KiSS1 in human osteosarcoma (OS). The aim of the present study was to investigate the role and molecular mechanisms of KiSS1 in human OS. The expression of KiSS1 was assessed by immunohistochemical assay using a tissue microarray procedure in forty cases of OS tissues. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Zhang et al . reported that KiSS1 functioned as a tumor suppressor in osteosarcoma cells through inhibition of the MAPK pathway 34 . In addition, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . reported that KiSS1 functioned as a tumor suppressor in osteosarcoma cells through inhibition of the MAPK pathway 34 . In addition, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 can release factors sequestered in the extracellular matrix, including VEGF, TGF-β and FGF-2, and stimulate proliferation and migration of endothelial cells [ 38 , 41 ]. It is evidenced that KiSS-1 can suppress MMP-9 expression [ 42 ]; we therefore tested whether our expressed protein had such activity. The results firmly confirmed that KiSS1 secreted from our recombinant L. lactis NZ9000-pNZ401-KiSS1 strain effectively downregulated the expression of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups used DNA microarray analysis to identify a cohort of 13 genes with elevated expression levels in the metastatic osteosarcoma samples when compared to primary tumors [ 23 , 24 ]. Among all those candidate genes, CD73 and IRF4 are closely related to the anti-oxidation of osteosarcoma cells and activation of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the animal model using DNA microarray analysis found 7 genes with significant expressional variations between higher metastatic and lower metastatic sub-groups of osteosarcoma cells. Some of those genes are correlated with the proliferation and invasion ability of tumors [ 23 , 24 ]. Past studies reported that PMP22 mainly exerted its functions in the motor-sensory neuropathy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%